A preparation method of flexible strain sensor based on AgNWs-MXene

By introducing AgNWs and MXene into PDMS and SEBS flexible substrates, AgNWs/MXene/PDMS and AgNWs/MXene/SEBS flexible strain sensors were prepared, which solved the shortcomings of traditional strain sensors in tensile performance and sensitivity, achieved high sensitivity and good cycling durability, and was suitable for human motion monitoring.

CN114963962BActive Publication Date: 2025-04-11CHANGCHUN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210523818.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-13
Publication Date
2025-04-11
Estimated Expiration
2042-05-13

AI Technical Summary

Technical Problem

Traditional rigid structural strain sensors have shortcomings in tensile performance and sensitivity, which limit their application in multiple fields.

Method used

AgNWs/MXene/PDMS and AgNWs/MXene/SEBS flexible strain sensors were prepared by introducing silver nanowires (AgNWs) and MXene as conductive materials into polydimethylsiloxane sponges (PDMS) and triblock copolymer poly(styrene-ethylene-butylene styrene) (SEBS) flexible substrates, respectively.

Benefits of technology

It achieves a sensitivity of 4.624 under pressure of 35-50kPa, and a sensitivity of up to 7.899 under 50-60% strain conditions, and shows excellent sensing stability and cycling durability within the 10%-50% strain range, which is suitable for human motion monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114963962B_ABST
    Figure CN114963962B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a flexible strain sensor based on AgNWs-MXene, which belongs to the field of flexible sensors. AgNWs and MXene are composited as sensitive materials and respectively combined with flexible substrate materials polydimethylsiloxane (PDMS) and triblock copolymer poly(styrene-ethylene-butylene styrene) (SEBS) to obtain two flexible strain sensors. The prepared strain sensors have the advantages of high sensitivity, high linearity, good stability, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of flexible sensors, and in particular relates to a method for preparing a flexible strain sensor by introducing silver nanowires (AgNWs) / MXene as conductive materials into polydimethylsiloxane sponge (PDMS) and triblock copolymer poly (styrene-ethylene-butylene styrene) (SEBS) flexible substrates respectively. Background Art

[0002] Nanomaterials have excellent performance in mechanical properties, electrical properties, thermal conductivity, etc., so combining conductive nanomaterials with flexible material substrates to prepare flexible strain sensors has become a research hotspot. AgNWs have unique antioxidant ability and excellent conductivity; MXene, as a new type of conductive nanomaterial, has a sheet structure similar to graphene, has excellent conductivity, and has rich groups on the surface, which is easy to surface treat. Based on the above background, combining AgNWs, MXene and flexible substrates, combining the performance advantages of both, and preparing new flexible sensing materials is of great significance for improving the performance of flexible sensors.

[0003] A sensor is a detection device that integrates detection, collection, transmission, and conversion. It can convert external stimulation to it into electrical signals and transmit them to the collection device, and by organizing and analyzing the collected data, it can depict the external stimulation to the sensor. Traditional rigid structure strain sensors are limited in many fields due to their own material properties, poor tensile properties, and low sensitivity. However, due to their structural and material characteristics, the new flexible strain sensor has mechanical properties far exceeding those of rigid sensors and excellent biocompatibility, which can meet working requirements that traditional sensors cannot meet. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a flexible strain sensor based on AgNWs / MXene and a flexible substrate material. The preparation method is simple and practical, and a flexible strain sensor based on AgNWs / MXene can be obtained.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a flexible strain sensor based on AgNWs-MXene comprises the following steps:

[0007] 1) Soak the sugar cube in PDMS and perform vacuum treatment in a vacuum drying oven for 30 to 150 minutes to allow the PDMS to fully fill the holes of the sugar cube, then take it out, clean the surface, dry it and solidify it, and obtain a PDMS sponge after ultrasonic treatment;

[0008] 2) Mixing MXene with N,N-dimethylformamide and dimethyl sulfoxide, soaking the PDMS sponge prepared in step 1) in the mixed solution under ultrasonic conditions for 10 minutes, and then drying in a forced air drying oven at 60° C. for 1 hour, repeating 6 times to obtain a MXene / PDMS sponge;

[0009] 3) Mixing AgNWs with anhydrous ethanol, soaking the MXene / PDMS sponge prepared in step 2) under ultrasonic conditions for 10 minutes, drying in an oven at 60° C. for 30 minutes, and repeating 6 times to obtain an AgNWs / MXene / PDMS sponge;

[0010] 4) Conductive silver paste is coated on both sides of the sponge obtained in step 3), and copper sheets are fixed with conductive epoxy resin as electrodes to obtain a flexible strain sensor, wherein the flexible strain sensor is an AgNWs / MXene / PDMS pressure sensor.

[0011] Preferably, the vacuum treatment in the vacuum drying oven in step 1) is performed for 90 minutes, the drying and curing is performed at 120° C. for 1 hour, and the ultrasonic treatment is performed at 40° C. for 1 hour.

[0012] Preferably, in step 2), 0.25 mL of N,N-dimethylformamide and 0.25 mL of dimethyl sulfoxide are used per mg of MXene.

[0013] Preferably, in step 3), 0.5 mL of anhydrous ethanol is used per mg of AgNWs.

[0014] A method for preparing a flexible strain sensor based on AgNWs-MXene comprises the following steps:

[0015] 1) SEBS and cyclohexane are mixed in a beaker, magnetically stirred until completely dissolved, and then the cyclohexane is completely evaporated by drying to obtain a SEBS flexible substrate;

[0016] 2) Place SEBS and cyclohexane in a beaker, stir magnetically until completely dissolved, add MXene and AgNWs and stir evenly to obtain a conductive solution;

[0017] 3) The SEBS flexible substrate prepared in step 1) is stretched to a strain of 100% to 500%, and the conductive solution prepared in step 2) is coated on both sides of the substrate, and dried naturally to obtain a sandwich structure of conductive filler / flexible substrate / conductive filler. Conductive tapes are adhered on both sides of the device as electrodes to obtain a flexible strain sensor, wherein the flexible strain sensor is an AgNWs / MXene / SEBS stretching sensor.

[0018] Preferably, in step 1), the mass volume ratio of SEBS to cyclohexane is 3 g:40 mL; and in step 2), the mass volume ratio of SEBS to cyclohexane is 1 g:20 mL.

[0019] Preferably, in step 2), 0.05 g MXene and 0.05 g AgNWs are used per mL of dissolved solution.

[0020] Preferably, in step 3), the SEBS flexible substrate is stretched to 200% strain before coating the conductive solution.

[0021] Beneficial effects:

[0022] The AgNWs / MXene / PDSM pressure sensor prepared by the present invention has better sensing performance than the sensor with a single conductive filler. Under a pressure of 35-50kPa, the sensitivity can reach 4.624, and under a strain of 50-60%, the sensitivity can reach a maximum of 7.899. And in the strain range of 10%-50%, it has excellent sensing stability in the face of different strain gradients. Under a pressure of 30kPa, it can maintain 1000 cycles while keeping the current change rate basically unchanged. This proves that the AgNWs / MXene / PDMS pressure sensor has excellent conductivity, high sensitivity and good cycle durability, and can be competent for certain human motion monitoring. And verified its ability to analyze the force of the foot when people are running, which can also prove that it has broad application prospects in the field of human motion detection.

[0023] The AgNWs / MXene / SEBS tensile sensor prepared by the present invention has GF values ​​of 69.033, 84.811, and 124.938 under strain conditions of 20%, 50%, and 80%, respectively. At the same time, stable sensing data output can be achieved in the small strain range of 0.5-5% and the large strain range of 5-50%. It can sensitively monitor the movement of the throat and hand joints, and has great application potential in the field of human motion monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Attached Figure 1 It is a sensitivity-pressure curve diagram of the flexible pressure sensor prepared by the present invention.

[0025] Attached Figure 2 This is a test chart of the cyclic durability of the flexible pressure sensor prepared by the present invention.

[0026] Attached Figure 3 It is a test photograph of the flexible pressure sensor array prepared by the present invention when a weight is pressed in the middle of a glass plate and a bar graph of the current change rate.

[0027] Attached Figure 4It is a test photograph of the flexible pressure sensor array prepared by the present invention when a weight is pressed on the lower right corner of a glass plate and a bar graph of the current change rate.

[0028] Attached Figure 5 It is a stress-strain curve diagram of the flexible tensile sensor prepared by the present invention.

[0029] Attached Figure 6 It is a sensitivity-strain curve diagram of the flexible stretch sensor prepared by the present invention.

[0030] Attached Figure 7 It is a physical picture of the flexible stretch sensor array test prepared by the present invention and a bar graph of the resistance change rate. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further explained and illustrated by way of specific embodiments below.

[0032] Example 1: Preparation of AgNWs / MXene conductive materials

[0033] 1.5 g of PVP with a molecular weight of 1300000 was added to 150 mL of ethylene glycol, dissolved under magnetic stirring at 90 ° C, and cooled to room temperature after dissolution. A 600 μM FeCl3·6H2O ethylene glycol solution was prepared, and 0.22 g of silver nitrate was weighed and dissolved in 8 mL of ethylene glycol. 20 mL of the prepared PVP solution was placed in a 100 mL beaker, 3 mL of ferric chloride solution was added and magnetically stirred evenly, and then the dissolved silver nitrate solution was added. After stirring evenly, it was poured into a polytetrafluoroethylene liner, and the reactor was installed and placed in a preheated oven at 130 ° C for 6 hours. After the reaction was completed, the reactor was taken out and placed in water for cooling. The viscous yellow-white product was washed with acetone and anhydrous ethanol to remove most of the nanoparticles. It was centrifuged and washed with anhydrous ethanol for 4-5 times. The washed product was dispersed in anhydrous ethanol to obtain a pure AgNWs dispersion, and the AgNWs powder was obtained by vacuum filtration through a sand core filter device.

[0034] Slowly add 3g Ti3AlC2 to 40mL 40% HF, place in a fume hood, and react for 3.5 hours. After the reaction, select deionized water as the cleaning liquid, use a desktop high-speed centrifuge to centrifuge at 3500r / min for 5 minutes, and centrifuge and wash 5-6 times until the pH is > 6. Collect the black precipitate after centrifugation in a plastic beaker and redisperse it in deionized water. Filter and collect the filtered black powder with a sand core suction filter. Place the obtained black powder in a vacuum drying oven and dry it at 60°C for 3 hours to obtain dry MXene powder.

[0035] Example 2: Preparation of AgNWs / MXene / PDMS pressure sensor

[0036] Prepare about 25g of AB agent of PDMS at a mass ratio of 1:10 and stir for 5 minutes to mix evenly. Use a vacuum oven to vacuum dry at 23kPa for 90 minutes to remove bubbles. Soak the sugar cube in PDMS and dry it in a vacuum oven for 90 minutes to fill the pores of the sugar cube with PDMS. After taking it out, clean the surface, dry it at 120℃ for 1 hour to solidify it, and then ultrasonicate it at 40℃ for 1 hour to obtain a PDMS sponge.

[0037] The prepared PDMS sponge needs to be combined with a conductive filler. 200 mg of MXene prepared in Example 1 is mixed with 50 mL of N,N-dimethylformamide and 50 mL of dimethyl sulfoxide, and the PDMS sponge is immersed in the mixed solution under ultrasonic conditions for 10 minutes, and then dried in a blast drying oven at 60°C for 1 hour, and repeated 6 times; then 200 mg of AgNWs prepared in Example 1 is mixed with 100 mL of anhydrous ethanol, and the prepared MXene / PDMS sponge is immersed in ultrasonic conditions for 10 minutes, and dried in an oven at 60°C for 30 minutes. The same is repeated 6 times to prepare an AgNWs / MXene / PDMS sponge, and conductive silver paste is coated on both sides of the sponge, and a copper sheet is fixed with a conductive epoxy resin as an electrode to prepare an AgNWs / MXene / PDMS pressure sensor.

[0038] Example 3: AgNWs / MXene / PDMS pressure sensor sensitivity-pressure curve test

[0039] Instrument model: CHI660E electrochemical workstation, ZP-50 push-pull force gauge. Sample preparation: The sensor sample prepared in Example 1 was cut into a size of 10 mm in length, 10 mm in width, and 10 mm in height. Test conditions: The compression rate was 1 mm / s.

[0040] Test results such as Figure 1 As shown in the figure, it can be seen that in the process of applying pressure, the current change rate of the pressure sensor will change to a certain extent. In the range of 0-30kPa, the change rate increases slowly. After 30kPa, the current change rate changes more obviously, showing a higher change rate.

[0041] Example 4: Cyclic durability test of AgNWs / MXene / PDMS pressure sensor

[0042] Instrument model: CHI660E electrochemical workstation, linear motor. Test conditions: external pressure 30kPa; cycle frequency: 30min -1 ; Cycle test time: 30 min; Gauge length: 10 mm. Sample preparation: The sensor sample prepared in Example 1 was cut into a size of 10 mm in length, 10 mm in width, and 10 mm in height.

[0043] Test results such as Figure 2 As shown. It can be observed from the figure that the current change of the sensor shows reasonable stability and repeatability. After multiple compression-release processes, the sensor still maintains the symmetry of the change rate. There are two small pictures in the figure. The left and right pictures show the working content of the first 20 seconds and the last 20 seconds of all cycles respectively. It can be seen that the current change rate has been maintained between 23-25, with ultra-high cycle durability, which also proves that this pressure sensor can maintain long-term working efficiency and continuous signal output capabilities under certain external pressure conditions.

[0044] Example 5: Actual picture of AgNWs / MXene / PDMS pressure sensor array test and current change rate test

[0045] Instrument model: CHI660E electrochemical workstation. Sample preparation: The sensor sample prepared in Example 1 was cut into a size of 10 mm in length, 10 mm in width, and 10 mm in height; number of samples: 9; weight of the weight: 50 g.

[0046] The prepared pressure sensors were arranged in a 3*3 array, a piece of glass was laid flat on top, and a 50g weight was placed on the glass. The weights were placed at different positions above the sensor array, and the sensing conditions of the sensors under pressure at different positions were tested and analyzed. Figure 3 a is a photo of the weight being pressed in the middle of the glass plate. Figure 3 b is the bar graph of the current change rate of the sensor obtained at this position, Figure 4 a is a photo of the weight being pressed on the lower right corner of the glass plate. Figure 4 b The bar graph of the rate of change of the inductive current obtained at this position. Figure 3 and Figure 4 It can be seen that when the weight is placed in the middle, the sensor in the middle has the largest current change rate, which spreads outward in sequence; when the weight is pressed on the corner, the current change at the corner is the largest, and radiates downward toward the other corner. This phenomenon proves that this pressure sensor array can map pressure distribution.

[0047] Example 6: Preparation of AgNWs / MXene / SEBS tensile sensor

[0048] Mix 3g SEBS with 40mL cyclohexane in a 100mL beaker and stir magnetically for 3 hours until completely dissolved. Place the stirred clear solution in a fume hood and dry for 24 hours to completely evaporate the cyclohexane to obtain a SEBS flexible film, which is cut to obtain a 5*20mm SEBS flexible substrate. Place 2g SEBS and 40mL cyclohexane in a 100mL beaker and stir magnetically for 2 hours until completely dissolved. Take 10mL of the dissolved solution, add 0.5g MXene+0.5g AgNWs prepared in Example 1 and stir evenly to obtain a conductive solution. Stretch the prepared SEBS flexible substrate to 200% strain, apply the configured conductive solution gently on both sides of the substrate with a brush, dry naturally, and obtain a sandwich structure of conductive filler / flexible substrate / conductive filler. Adhere conductive tapes as electrodes on both sides of the device to obtain AgNWs / MXene / SEBS stretching sensor.

[0049] Example 7: Stress-strain curve test of AgNWs / MXene / SEBS tensile sensor

[0050] Instrument model: model AGS-X universal testing machine. Test conditions: tensile rate is 80 mm / min. Sample preparation: the sensor sample prepared in Example 6 is cut into a dumbbell shape, and the size of the dumbbell-shaped sample is 30 mm in length, 4 mm in width, 3 mm in thickness, and 12 mm in gauge length.

[0051] Through the mechanical properties analysis of AgNWs / MXene / SEBS tensile sensor, we can obtain Figure 5 The stress-strain curve shown shows the change of stress with strain in the sensor within the strain range of 0-500%. From the overall trend, it can be seen that as the strain increases, the rate of change of stress decreases, which means that as the flexible substrate is stretched, the internal structure is destroyed and the mechanical properties decrease, so the force required for the same amount of deformation is getting smaller and smaller. MXene is a two-dimensional layer structure, which is difficult to cross-link with each other, so the strength of the prepared sensor is low; AgNWs will produce some entanglement due to its high aspect ratio, resulting in an increase in membrane strength; by combining the two materials, MXene further increases the strength of the sensor by welding the nodes between AgNWs.

[0052] Example 8: AgNWs / MXene / SEBS tensile sensor sensitivity-strain curve test

[0053] Instrument model: CHI660E electrochemical workstation, model AGS-X universal testing machine. Test conditions: tensile rate: 80 mm / min; tensile length: 40 mm. Sample preparation: The sensor sample prepared in Example 6 was cut into a dumbbell shape, and the size of the dumbbell-shaped sample was 20 mm in length, 4 mm in width, and 3 mm in thickness.

[0054] The sensitivity of the sensor is analyzed by testing the resistance change of the sensor in the 0-100% strain range, and the following Figure 6 The sensitivity curve shown in the figure shows that when the strain reaches 100%, the sensitivity is as high as 176.25. AgNWs and MXene are cross-linked on the surface of the SEBS film. When strain occurs, the connection or breakage between the conductive fillers occurs more frequently, so the resistance change is more sensitive, making it have the maximum sensitivity. The overall sensitivity of the sensor increases with the increase of strain. This is because as the overall strain increases, the breakage between the conductive fillers becomes more obvious, and the resistance change rate increases, which leads to a change in sensitivity.

[0055] Example 9: Actual picture of AgNWs / MXene / SEBS stretch sensor array test and resistance change rate test

[0056] Instrument model: CHI660E electrochemical workstation. Sample preparation: The sensor sample prepared in Example 6 was cut into 8 mm in length, 8 mm in width, and 3 mm in thickness; number of samples: 16 pieces.

[0057] like Figure 7 As shown, Figure 7 a The AgNWs / MXene / SEBS stretch sensors are arranged into a 4*4 array and fixed to the wrist with tape. When the wrist moves, the deformation of the sensor varies due to the different tensions at different positions of the wrist, resulting in different resistance change rates. The electrical signals of the sensors in the array are collected and analyzed. Figure 7 b is a 3D array of the resistance change rate of the sensor. The four groups of sensors in the middle position have the largest resistance change rate because they are fixed at the point where the wrist has the largest range of motion. The sensors at the four edges have a relatively low resistance change rate because they are stretched to a smaller extent.

Claims

1. A method for preparing a flexible strain sensor based on AgNWs-MXene, comprising the following steps: 1) Soak the sugar cube in PDMS and perform vacuum treatment in a vacuum drying oven for 30 to 150 minutes to allow the PDMS to fully fill the holes of the sugar cube, then take it out, clean the surface, dry it and solidify it, and obtain a PDMS sponge after ultrasonic treatment; 2) Mixing MXene with N,N-dimethylformamide and dimethyl sulfoxide, soaking the PDMS sponge prepared in step 1) in the mixed solution under ultrasonic conditions for 10 minutes, and then drying in a forced air drying oven at 60° C. for 1 hour, repeating 6 times to obtain a MXene / PDMS sponge; 3) Mixing AgNWs with anhydrous ethanol, soaking the MXene / PDMS sponge prepared in step 2) under ultrasonic conditions for 10 minutes, drying in an oven at 60° C. for 30 minutes, and repeating 6 times to obtain an AgNWs / MXene / PDMS sponge; 4) Conductive silver paste is coated on both sides of the sponge obtained in step 3), and copper sheets are fixed with conductive epoxy resin as electrodes to obtain a flexible strain sensor, wherein the flexible strain sensor is an AgNWs / MXene / PDMS pressure sensor.

2. The method for preparing a flexible strain sensor based on AgNWs-MXene according to claim 1, characterized in that: In step 1), the vacuum treatment in the vacuum drying oven is performed for 90 minutes, the drying and curing is performed at 120° C. for 1 hour, and the ultrasonic treatment is performed at 40° C. for 1 hour.

3. The method for preparing a flexible strain sensor based on AgNWs-MXene according to claim 1, characterized in that: In step 2), 0.25 mL of N,N-dimethylformamide and 0.25 mL of dimethyl sulfoxide were used per mg of MXene.

4. The method for preparing a flexible strain sensor based on AgNWs-MXene according to claim 1, characterized in that: In step 3), 0.5 mL of anhydrous ethanol was used per mg of AgNWs.

5. A method for preparing a flexible strain sensor based on AgNWs-MXene, comprising the following steps: 1) SEBS and cyclohexane are mixed in a beaker, magnetically stirred until completely dissolved, and then the cyclohexane is completely evaporated by drying to obtain a SEBS flexible substrate; 2) Place SEBS and cyclohexane in a beaker, stir magnetically until completely dissolved, add MXene and AgNWs and stir evenly to obtain a conductive solution; 3) The SEBS flexible substrate prepared in step 1) is stretched to a strain of 100% to 500%, and the conductive solution prepared in step 2) is coated on both sides of the substrate, and dried naturally to obtain a sandwich structure of conductive filler / flexible substrate / conductive filler. Conductive tapes are adhered on both sides of the device as electrodes to obtain a flexible strain sensor, wherein the flexible strain sensor is an AgNWs / MXene / SEBS stretching sensor.

6. The method for preparing a flexible strain sensor based on AgNWs-MXene according to claim 5, characterized in that: The mass volume ratio of SEBS to cyclohexane in step 1) is 3 g:40 mL; the mass volume ratio of SEBS to cyclohexane in step 2) is 1 g:20 mL.

7. The method for preparing a flexible strain sensor based on AgNWs-MXene according to claim 5, characterized in that: In step 2), 0.05 g MXene and 0.05 g AgNWs were used per mL of dissolved solution.

8. The method for preparing a flexible strain sensor based on AgNWs-MXene according to claim 5, characterized in that: In step 3), the SEBS flexible substrate is stretched to 200% strain before coating the conductive solution.